Intelligent Distributed Computing XVI : 16th International Symposium on Intelligent Distributed Computing, IDC 2023 (Studies in computational intelligence, 2024)
This book presents selected contributions to the 16th Symposium on Intelligent Distributed Computing (IDC’23) held from September 13 to 15, 2023, at the HAW Hamburg, Germany. This unique collection of papers presents the latest findings, research achievements and ideas in the area of Intelligent Distributed Computing provided by researchers and practitioners from both distributed computing and intelligent computing communities. Distributed computing covers methods and technology to build complex computational systems composed of collaborating software components scattered across diverse computational elements. Intelligent computing offers a hybrid palette of methods, techniques and their applications ranging from classical artificial intelligence, information and data sciences, multi-agent technologies or computational intelligence to more recent trends such as swarm intelligence, bio-inspired computation, cloud computing, machine learning or social/cyber-physical trust and security.
Keywords: Intelligent Distributed Computing; Computational Intelligence; Internet of Things; Blockchain; Intelligent Transportation Systems; Data Analytics; Trust and Reputation Systems; Conference Proceedings; IDC 2023